Peroneus Brevis Muscle Flap as a Tissue Cover for Defect over Lower Mid Leg and Ankle Defects: A Case Series - Sanjay Gordhanbhai Vaghani (JCDR Research and Publications Private Limited, 2021)
Mid leg and ankle area are more vulnerable for post-traumatic full thickness soft tissue loss. Implants used in osteosynthesis in this region are also at risk of exposure as its placement is in subcutaneous plane as well as precarious blood supply in shin region. Various options like local flap to free flap are described for reconstruction of small and medium size defects in this region. Peroneus brevis is also well described in literatures. In this case series which was done over the period of six years that includes 10 patients with post-traumatic as well as post orthopaedics surgical intervention defects in lower mid leg and ankle region. Patients were selected for proximally and distally based peroneus brevis muscle flap according to the location of defects. Data regarding age, sex, aetiological factor, size of defect, type of flap, survival of flap, donor site complications were recorded. Out of 10 patients, eight were males and two were females. Major aetiological factor was two wheeler road traffic accident. Majority of the patient had orthopaedic surgical intervention for fracture fixation prior to or along with flap surgery. Only one patient, in this series had marginal flap necrosis. Rest of flaps survived well without any donor site complications. In authors experience peroneus brevis muscle flap is dependable for medium size defects over lower leg and ankle.